Analgesia of Epidural Tramadol in Dogs Submitted to Orchiectomy - de Almeida, Ricardo; Escobar, André [UNESP]; Maguilnik, Samara (Veterinary Solutions Llc, 2009)
Epidural tramadol in veterinary medicine has been studied in only a few instances. In this case, 36 dogs submitted to orchiectomy received 6.0 mg/kg of lidocaine combined with 1.0 mg/kg of tramadol, 0.1 mg/kg of morphine or 0.01 ml/kg of 0.9% NaCl by epidural route. Analgesia was assessed at 4, 8, 12, 18 and 24 hours after surgery. There were no differences between morphine and tramadol over the time of evaluation within these groups, and no complementary analgesia was necessary. In the NaCl group, analgesia was needed at 4, 8 and 12 hours. Epidural tramadol provides an analgesic effect comparable to that of morphine during the first 12 hours post-surgery.
Keywords: tramadol; morphine; analgesia; epidural; dog; orchiectomys